A Practical Hybrid Digital-Analog Scheme for Wireless Video Transmission - Lan, Cuiling; Luo, Chong; Zeng, Wenjun; Wu, Feng (IEEE Trans. on Cir. and Sys. for Video Technology, 2018)
We propose a hybrid digital-analog (HDA) framework for wireless video transmission, which benefits from both the high distortion-power performance of digital systems and the graceful performance degradation of analog systems. The proposed framework models video frames as a parallel Gaussian source, which is separated into digital and analog parts through scalar quantization. It features entropy coding and channel coding in digital transmission and power scaling in analog transmission. The key challenge in this framework is how to allocate the constrained power and bandwidth resources between and among digital and analog components to achieve minimal distortion at the receiver. Given the worst-case CSNR, we are able to derive a closed-form expression of the overall distortion. However, minimizing it is a mixed-integer non-linear programming problem which is generally NP-hard. By making reasonable and justified simplifications, we approach the optimal solution through a practical scheme. Evaluations show that the proposed scheme outperforms the state-of-the-art analog scheme SoftCast by a large margin. The gain in received video PSNR is up to 5.0dB for various types of videos.